The Role Of Digital Marketing In Crisis Management - غدير باسم; إسبر لمى; محمد أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of the research is to study the role of digital marketing in crisis management, by studying the role of the digital marketing dimensions: Attracting, Relating, Engaging, Learning and Retaining in crisis management. The researcher relied on the descriptive analytical approach as a general approach to research, where a questionnaire was designed and distributed to an intentional sample (number 70, 64 questionnaires were retrieved valid for statistical analysis) from small and medium enterprises in the governorate of Damascus that exercise part of their work in the digital environment, and the researcher used the statistical program Spss In conducting statistical descriptions and testing research hypotheses. The research found that there is a positive moral effect of digital marketing in crisis management for the projects under discussion, and the ranking of the dimensions of digital marketing in terms of the power of influence in crisis management for the enterprises under discussion, according to the following order: Relating, Retaining, Attraction, Engaging, learning.